Pengaruh Elemen Desain Kemasan Produk Sari Lemon Kayu Manis Le_Cinnamon Terhadap Minat Beli Konsumen - Lathifah, Rizka Ayumi; Fatimah, Sri (Universitas Galuh, 2024)
Since the function of packaging has developed into a medium of marketing communication with visual appeal, every producers must pay attention to their product packaging. It is necessary because a product packaging can be “the silent salesman” that able to introduce, persuade, and attract consumers to buy its product. This research aims to determine the influence product packaging design on consumer purchase intention of Le_Cinnamon, which an agribusiness innovation product that produce in Bandung, West Java. Descriptive quantitative methods with multiple linear regression analysis were used in this study to analyze product packaging design Le_Cinnamon from its three constituent elements, such as graphic design, design structure, and product information to see its influence on consumer purchase intention. Questionnaire data was obtained from 131 respondents used in this study, where the research sample was determined by stratified random sampling. From this study, results were obtained that showed three elements of packaging design on Le_Cinnamon products, such as graphic design, design structure, and product information had a significant effect with a percentage of 68.7% on consumer purchase intention.